Дослідження деформації професійної правосвідомості юриста - Куренда, Л.; Kurenda, L. (Східноєвропейський національний університет імені Лесі Українки, 2013)
У матеріалах наукової статті досліджується поняття деформації професійної правосвідомості юриста, дається коротка характеристика основних видів деформації професійної правосвідомості. На цій основі формуються практичні пропозиції із позиції багатолітнього педагогічного досвіду викладання у вищих навчальних закладах, із розмежування типів майбутніх юристів, які є носіями деформованої правосвідомості.The author explores the concept of the deformation of the professional legal awareness and gives a brief analysis of the main types of such phenomenon. The deformations of the professional legal awareness on the motivational level are particularly dangerous. In this regard, one can distinguish the following types of lawyers who are carriers of a deformed sense of legal awareness: «рragmatic» understands the spirit and the letter of the law, but is primarily interested in the «passing» of the case and in this regard focuses on the opinion of those upon which the final solution of the matter depends. «Weather vane» allows derogation from the requirements of the law under the managers’ pressure. «Pedant» is very strongly guided by the letter of the law, but it may yield to the spirit of respect for the sake of form, «antipedant» is guided by the spirit of the law but may be inferior to the letter, «climber» tends to give way to the law for the sake of promotion, «bureaucrat» skulks behind the law and does not notice the letter of the law, or dilutes its spirit for the sake of his own convenience and peace of mind, «a fictitious lawyer» violates the law for personal gain.
The Study of the Deformation of the Professional Legal Awareness
Keywords: правосвідомість; деформація; професія; юрист; нігілізм; інфантилізм; professional legal awareness; deformation; a profession; a lawyer; nihilism; infantilism